Telomere-Related Disorders in Fetal Membranes Associated With Birth and Adverse Pregnancy Outcomes - Polettini, Jossimara; da Silva, Marcia Guimarães [UNESP] (Frontiers, 2020)
Telomere disorders have been associated with aging-related diseases, including diabetes, vascular, and neurodegenerative diseases. The main consequence of altered telomere is the induction of the state of irreversible cell cycle arrest. Though several mechanisms responsible for the activation of senescence have been identified, it is still unclear how a cell is indeed induced to become irreversibly arrested. Most tissues in the body will experience senescence throughout its lifespan, but intrinsic and extrinsic stressors, such as chemicals, pollution, oxidative stress (OS), and inflammation accelerate the process. Pregnancy is a state of OS, as the higher metabolic demand of the growing fetus results in increased reactive oxygen species production. As a temporary organ in the mother, senescence in fetal membranes and placenta is expected and linked to term parturition (>37 weeks of gestation). However, a persistent, overwhelming, or premature OS affects placental antioxidant capacity, with consequent accumulation of OS causing damage to lipids, proteins, and DNA in the placental tissues. Therefore, senescence and its main inducer, telomere length (TL) reduction, have been associated with pregnancy complications, including stillbirth, preeclampsia, intrauterine growth restriction, and prematurity. Fetal membranes have a notable role in preterm births, which continue to be a major health issue associated with increased risk of neo and perinatal adverse outcomes and/or predisposition to disease in later life; however, the ability to mediate a delay in parturition during such cases is limited, because the pathophysiology of preterm births and physiological mechanisms of term births are not yet fully elucidated. Here, we review the current knowledge regarding the regulation of telomere-related senescence mechanisms in fetal membranes, highlighting the role of inflammation, methylation, and telomerase activity. Moreover, we present the evidences of TL reduction and senescence in gestational tissues by the time of term parturition. In conclusion, we verified that telomere regulation in fetal membranes requires a more complete understanding, in order to support the development of successful effective interventions of the molecular mechanisms that triggers parturition, including telomere signals, which may vary throughout placental tissues.
Keywords: gestation; membrane premature rupture; oxidative stress; parturition; prematurity; telomere shortening